2000
DOI: 10.1017/s1357729800051560
|View full text |Cite
|
Sign up to set email alerts
|

Continued selection of Romney sheep for resistance or susceptibility to nematode infection: estimates of direct and correlated responses

Abstract: Divergent breeding lines of Romney sheep, selected as lambs for consistently high or low faecal worm egg count (FEC) following natural multi-species challenge by nematode parasites, were established in New Zealand at Wallaceville Animal Research Centre in 1979 and at Rotomahana Station in 1985. In 1988 the Rotomahana lines, including an unselected control line maintained under the same management conditions, were transferred to Tokanui Station where they remained for 4 years. In 1993 elite high and low FEC ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 14 publications
8
60
1
4
Order By: Relevance
“…Morris et al (2010) reported a non-significant genetic correlation between FWEC and litter size. However, a small correlated genetic response to FWEC selection was observed in another study by Morris et al (2000), with litter size being greater (i.e. 0.11 more lambs weaned/ewe) in the parasite-resistant line than the control line.…”
Section: Discussionmentioning
confidence: 85%
“…Morris et al (2010) reported a non-significant genetic correlation between FWEC and litter size. However, a small correlated genetic response to FWEC selection was observed in another study by Morris et al (2000), with litter size being greater (i.e. 0.11 more lambs weaned/ewe) in the parasite-resistant line than the control line.…”
Section: Discussionmentioning
confidence: 85%
“…Although studies have shown that increased dag scores are associated with decreased FEC (Morris et al, 2000(Morris et al, , 2005, one study in the UK suggests that at mid to late summer the situation is reversed, with a positive correlation between increased dag score and high FEC in lambs (Broughan and Wall, 2007). A recent study conducted in Western Australia used scouring as the primary and weight gain as secondary indicators to target anthelmintic treatments in groups of 12-month old Merino sheep.…”
Section: Dag Scoresmentioning
confidence: 99%
“…Morris et al (7) observaram taxa de natalidade 11% maior em ovelhas resistentes (selecionadas por reprodução seletiva) quando comparadas às selecionadas para alto OPG; entretanto, os autores encontraram correlação genética desfavorável entre OPG e ganho de peso quando animais resistentes e sensíveis foram mantidos na mesma pastagem. Independentemente do grau de resistência, a concentração das mortes de ovelhas ocorreu no periparto-lactação (Tabela 2), fase caracterizada por aumento expressivo na exigência de proteína metabolizável (29) e diminuição da resistência à verminose, coincidindo com o período de transição águas-seca, época de baixa disponibilidade e qualidade das pastagens na região (Figura 1 e Tabela 3).…”
Section: Resultsunclassified
“…O desenvolvimento de linhagens de ovinos resistentes às verminoses pela reprodução seletiva tem sido utilizado na Austrália e Nova Zelândia. Investigação de campo, contudo, tem resultado tanto em relações favoráveis quanto desfavoráveis entre as características de produção e maior resistência aos parasitas (6)(7)(8) . O desenvolvimento de uma resposta imune competente contra os nematodas está associado negativamente com a eficiência nutricional como anorexia e mudanças nas rotas metabólicas, que são questões levantadas quando se busca o fortalecimento da resposta imune pela seleção genética (9) .…”
Section: Fernandes Lh Et Alunclassified